Effect of Guided Discovery learning model in mastering of Force and Motion subject - Parno P (Department of Physics, Sebelas Maret University, 2015)
This research aims to describe students’ mastering of the basic concept about Force and Motion through the Guided Discovery learning model. This research uses pre-experimental one-group pretest-post test design. The research subjects are 25 students in sixth semester in the physics education department who are taking the Capita Selecta of School Physics course. This research uses the Basic Concept Mastering about Forceand Motion Test, and the Students Response Questionnaire for Learning Process instruments. The test data is analyzed using an average normalized gain secure, andthe question naire data are analyzed descriptively. The results show that student (1) has an average of mastering of the basic concept 75.38, an average normalized gain score of individual 0.556 that is smaller than an average normalized gain score of class 0.568 (medium category), and (2) gives a positive response for the learning process, namely 58.33% agree and 38.22% strongly agree, on the Force and Motion topic.